The Art of Living With Symptoms: A Qualitative Study Among Patients With Primary Brain Tumors Receiving Proton Beam Therapy. Issue 2 (March 2020) - Langegård, Ulrica; Ahlberg, Karin; Björk-Eriksson, Thomas; Fransson, Per; Johansson, Birgitta; Ohlsson-Nevo, Emma; Witt-Nyström, Petra; Sjövall, Katarina
Abstract : Background: Symptom management in conjunction with proton beam therapy (PBT) from patient's perspective has not been explored. Such knowledge is essential to optimize the care in this relatively new treatment modality. Objective: The aim of this study was to explore the process of symptom management in patients with brain tumor receiving PBT. Methods: Participants were 22 patients with primary brain tumor who received PBT, recruited in collaboration with a national center for proton therapy and 2 oncology clinics at 2 university hospitals in Sweden. Interviews using open-ended questions were conducted before, during, and/or after treatment. Verbatim interview transcripts were analyzed using classic Grounded Theory. Results: " The art of living with symptoms" emerged as the core concept. This encompassed 3 interconnected symptom management concepts: "Adapting to limited ability, " "Learning about oneself, " and "Creating new routines." These concepts were summarized in a substantive theoretical model of symptom management. Despite the struggle to manage symptoms, participants lived a satisfactory life. Conclusions: Symptom management in conjunction with PBT comprises a process of action, thoughts, and emotions. The concepts that emerged indicated patients' symptom management strategies were based on their own resources. Implications for Practice: It is important that PBT facilities develop an approach that facilitates the symptom management process based on patients' experiences of symptoms, as well as their actions and available resources.